(untitled) (Bangladesh Agronomy Journal, 2025)
A field experiment was conducted at the Agronomy Research Field, Gazipur, RARS, Jamalpur, RARS, Jashore, RARS, Burirhat, HARS, Hathazari, ARS, Rajbari and OFRD, Shyampur of Bangladesh Agricultural Research Institute, during rabi season of 2022-23 to study the effect of yield and yield contributing characters of chia seeds as affected by sowing date and spacing at different location. The experiment consisted of four sowing dates viz. (15 Nov., 30 Nov., 15 Dec. and 30 Dec.) and two spacing viz. (30 cm × continuous in solid line and 40 cm × continuous in solid line). Sowing date showed great influence on total dry matter (TDM) production, leaf area index (LAI), yield and yield components of chia. The November sowing produced the maximum TDM and LAI at Gazipur. These parameters finally contributed to higher seed yield in early planting than later sowing date. The days required for the events of maturity (109 days,108 days,106 days, 112 days, 108 days, 110 days and 108 days at Gazipur, Jamalpur, Jashore, Burirhat, Hathazari, Rajbari and Shyampur, respectively) was obtained from 15 November sowing. It was also found that 15 November sowing with 30 cm row spacing produced the higher yield (1059.41 kg ha−1, 823.80 kg ha−1, 849.42 kg ha−1, 1037. 94 kg ha−1 and 828.64 kg ha−1 at Gazipur, Jamalpur, Jashore, Burirhat and Hathazari, respectively) but at Rajbari and Shyampur produced the highest yield in 15 November sowing with 40 cm row spacing (1273 kg ha−1 and 1327.00 kg ha−1). The results revealed that November sowing produced higher yield might be due to favourable air temperature for growth and development of chia. Late sowing after November 30 produced lower yield due to high temperature prevailed at the later growth stage (March) of chia at all locations. Results revealed that November sowing with 30 cm × continuous in solid line performed better and with the advancement of sowing dates the temperature increased reduced the grain growth duration and decreased the seed yield. The results revealed that November 15 to November 30 sowing would be the optimum sowing date for chia in relation to air temperature. The temperature co-efficient of chia was estimated at 131.81 kg ha−1 decreased per increasing 1 °C air temperature. Effect of temperature on the seed yield of chia was estimated at 74-94 %. Bangladesh Agron. J. 2025, 28(1): 35-45